Air filled, including "air‐charged, " catheters in urodynamic studies: does the evidence justify their use?. Issue 5 (31st August 2016) - Abrams, Paul; Damaser, Margot S.; Niblett, Philip; Rosier, Peter F.W.M.; Toozs‐Hobson, Philip; Hosker, Gordon; Kightley, Robert; Gammie, Andrew
Abstract : Aims: Air filled catheters (AFCs) have been actively marketed for the past few years and in some geographic areas are widely used. However, as the scientific basis for introduction of this technology for pressure measurement in urodynamics was not clear, a study group examined the evidence. Methods: A search of the peer reviewed literature was carried out. Results: Four papers were identified, of which two were laboratory experiments and two were clinical papers, in female patients, that compared the pressures recorded by AFCs and those recorded using the traditional water filled catheters (WFCs). These data show that there are differences between the pressures measured by the two types of catheters. As yet, the reasons for these differences are not clear. Conclusions: There should be further systematic laboratory and clinical research before AFCs can be recommended for routine clinical use. We would recommend that a professional worldwide multidisciplinary scientific society, such as the International Continence Society, should work with manufacturers and regulatory bodies to ensure that this urodynamic method is properly scientifically evaluated, in the wider interests of patient safety.